EVALUASI KUALITAS LAYANAN WEBSITE PRIMARYCARE VAKSIN BPJS MENGGUNAKAN WEBQUAL 4.0 DAN IMPORTANCE-PERFORMANCE ANALYSIS (IPA) (Studi Kasus: FKTP Jakarta) - Dwi Hadiyanti, (2022)
BPJS Kesehatan plays an important role in supporting the reduction in the number of Covid-19 cases in Indonesia, one of which is vaccination efforts through the use of the PrimaryCare Vaccine website. The PrimaryCare Vaccine website is a website created by BPJS to facilitate First Level Health Facilities (FKTP) in collecting data on vaccination participants. There are several problems that exist on the website. Respondents are indicated for vaccinator admins and officers who access the PrimaryCare Vaccine website as users. Based on the problems that exist on the PrimaryCare Vaccines website, the measurement of evaluating the quality of website services on user satisfaction is appropriate, namely the webqual 4.0 method and the importance performance analysis (IPA) method. Data were collected from questionnaires and tested for reliability and validity on the calculated sample data. The reliability test shows Cronbach's Alpha value is 0.953 with N of Items 38, the value states if > 0.6 then the data is reliable. The validity test shows that the value generated in the Corrected Item-Total Correlation has no value below 0.1149 (rtable), then the data in each statement is valid. The results of the analysis in this study can be used as material for recommendations and evaluations for BPJS Health as a form to determine future strategies in developing good service quality on the PrimaryCare Vaccine website.